2014
DOI: 10.1094/pdis-11-13-1115-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Clover yellow vein virus on Glycine max in Korea

Abstract: Glycine max (Soybean) is the most important edible crop in Korea. In Korea, eight viruses have been reported to infect soybean, including Alfalfa mosaic virus (AMV), Cowpea mosaic virus (CPMV), Cucumber mosaic virus (CMV), Soybean dwarf virus (SbDV), Soybean mosaic virus (SMV), Soybean yellow common mosaic virus (SYCMV), Soybean yellow mottle virus (SYMMV), and Peanut stunt virus (PSV) (1). In 2012, Glycine max were observed in Daegu, South Korea, with mosaic and mottling symptoms on leaves. Samples with virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The obtained complete genome sequence of WVMV isolate JEBU was very different from that from wisteria species [ 38 ]. Although several other viruses, including alfalfa mosaic virus (AMV), cowpea mosaic virus (CPMV), soybean dwarf virus (SbDV), and clover yellow vein virus (ClYVV), infecting soybean plants have been identified in Korea [ 39 ], we did not find any viral sequences associated with those viruses, suggesting that they are not major viruses infecting soybean in Korea.…”
Section: Discussionmentioning
confidence: 77%
“…The obtained complete genome sequence of WVMV isolate JEBU was very different from that from wisteria species [ 38 ]. Although several other viruses, including alfalfa mosaic virus (AMV), cowpea mosaic virus (CPMV), soybean dwarf virus (SbDV), and clover yellow vein virus (ClYVV), infecting soybean plants have been identified in Korea [ 39 ], we did not find any viral sequences associated with those viruses, suggesting that they are not major viruses infecting soybean in Korea.…”
Section: Discussionmentioning
confidence: 77%
“…The two ClYVV isolates were detected in fields in two different counties in central and southeastern Iowa, USA in 2016 and 2017, respectively. Sequencing and phylogenetic analysis showed that ClYVV IA-2016 and ClYVV IA-2017 shared 96.5% nt sequence identity and were most closely related to ClYVV I89-1 (Japan) and ClYVV-Gm (South Korea), the latter of which was also found in soybean [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is clover yellow vein virus (ClYVV), a potyvirus that is primarily known to cause important diseases in forage legumes [ 23 ]. ClYVV was recently reported in field-grown soybeans in South Korea, and a partial genome was found in an RNA sequencing study performed with soybean samples collected in Ohio, USA [ 24 , 25 ]. Although soybean is not normally considered as a host to ClYVV, a recent report showed wild soybeans ( Glycine soja ) were susceptible to ClYVV in contrast to cultivated soybeans ( Glycine max ) that were resistant to the ClYVV isolates tested [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the soybean mosaic virus (SMV), the soybean yellow mottle mosaic virus (SYMMV), and the soybean yellow common mosaic virus (SYCMV) have been identified as major viruses infecting soybean in Korea [7]. Other viruses infecting soybean in Korea include the peanut mottle virus (PeMV), the soybean dwarf virus, the clover yellow vein virus, the bean common mosaic virus, the peanut stunt virus, the tomato spotted wilt virus, and the bean common mosaic necrosis virus [8][9][10][11][12][13][14]. Although various RNA viruses infecting soybean have been identified, none of the DNA viruses infecting soybean have been reported in Korea.…”
Section: Introductionmentioning
confidence: 99%